'LONESOME TOWN'? IS LONELINESS ASSOCIATED WITH THE RESIDENTIAL ENVIRONMENT, INCLUDING HOUSING AND NEIGHBORHOOD FACTORS?. Issue 7 (September 2015) - Kearns, Ade; Whitley, Elise; Tannahill, Carol; Ellaway, Anne
<x xml:space="preserve">Abstract</x> This article considers whether feelings of loneliness are associated with aspects of the home and neighborhood of residence. Multinominal logistic regression models were used to explore associations between residential environment and loneliness in 4, 000 residents across deprived areas of Glasgow. People who rated their neighborhood environment of higher quality and who used more local amenities were less likely to report loneliness. Respondents who knew more people within the local area were less likely to report loneliness. Those who reported more antisocial behavior problems, who had a weak perception of collective efficacy, and who felt unsafe walking alone at nighttime were more likely to report loneliness. Length of residence and dwelling type were not associated with reported loneliness. The findings indicate the potential importance of several dimensions of the neighborhood physical, service, and social environment, including aspects of both quality and trust, in protecting against or reducing loneliness in deprived areas.